Anterior cruciate ligament (ACL) reconstruction– A numerical case study. Issue 1 (31st December 2022) - Bhat, Bharath K; Adhikari, Raviraja; V Acharya, Kiran Kumar
Abstract: ACL reconstruction is the recommended surgery for young, physically active persons with complete ACL rupture. This study has MAHE, Manipal ethics committee clearance. This research is a case study on AMP and TT techniques of ACL reconstruction. The two techniques of Reconstruction of ACL undertaken on different subjects are compared with the healthy knee joint and Reconstructed-ACL (R–ACL) which have undergone simulation, based on the stress induced. This research paper is based on a retrospective study that utilizes image data from previously carried–out surgery on patients and does not cause any harm to the living condition of the patients. Computer Tomography (CT) image of the human knee joint of a person who had undergone ACL reconstruction by Anteromedial Portal (AMP) technique and another person who had undergone ACL reconstruction by Traditional Transtibial (TT) technique were considered for this study. A 3-dimensional (3D) geometry of the reconstructed ACL is generated from the CT images of human knee joints of both persons. A Magnetic Resonance Image (MRI) of a healthy human knee joint is considered. A 3-D geometric image of this healthy human knee joint is considered. It is discretized into a finite element model. The healthy ACL was replaced by a reconstructed ACL in the healthy human knee joint. The loads and boundary conditions corresponding to the Lachman test were applied to the human knee joint. In this study, equivalent stress (Von-Mises) in the ACL reconstructed by the AMP technique was found to be 16.07 MPa, whereas the equivalent stress in the ACL which has undergone TT technique of ACL reconstruction was 36.73 MPa. The equivalent stress distribution in the model was assessed and compared with earlier studies. Based on the analysis, it was found that the AMP technique is better than the TT technique of ACL reconstruction.